Modelling early iInitiation of HAART to forestall AIDS-related lymphoma in South Africa: a cost-effectiveness analysis. - Kyomugisha, Irene (Stellenbosch : Stellenbosch University, 2017)
Thesis (MSc)--Stellenbosch University, 2017.